Descendants of Cyrus : Travels through Everyday Iran - Thornton, Christopher (Book collections on Project MUSE., 2019)
A firsthand look at one of the least accessible and yet most politically significant countries on earth, Descendants of Cyrus taps is a beautifully written travelogue full of Iranian culture, history, and politics.